Assessing Estimates of Patient Safety Derived From Coded Data. Issue 4 (July 2017) - Narain, Wazim
Abstract : Abstract: The Agency for Healthcare Research and Quality (AHRQ) developed Patient Safety Indicators (PSI) with the goal of detecting and preventing adverse events using administrative data. Use of PSIs to measure safety and quality of care raises questions since they rely heavily on coded data. The goal of this paper is to review literature on AHRQ PSIs, specifically their accuracy in detecting adverse events, and how recent coding changes affect the accuracy of these estimates. The Healthcare Utilization Project (HCUP) National Inpatient Sample (NIS) contains data on more than seven million hospital stays yearly. Trending these estimates over time indicate there has been a decrease in rates for the majority of PSIs, with Accidental Puncture or Laceration, Central Venous Catheter Blood Stream Infections, Iatrogenic Pneumothorax, and Deaths from complications decreasing significantly each year from 2008–2012. Birth Trauma, Retained Foreign Bodies, Post-op Sepsis and Post-Op Respiratory Failure PSIs show no improvement from 2008–2012. A literature review on accuracy of PSIs and the affect of the Present on Admission (POA) indicator on PSI estimates reveals mixed results. PSIs serve as a useful tool in identifying problem areas in quality of care but should be used cautiously in determining hospital performance.